Expression cloning of a rat liver Na(+)-independent organic anion transporter. - Jacquemin, E (1994)
Using expression cloning in Xenopus laevis oocytes, we have isolated a cDNA encoding a rat liver organic anion-transporting polypeptide (oatp). The cloned oatp mediated Na(+)-independent uptake of sulfobromophthalein (BSP) which was Cl(-)-dependent in the presence of bovine serum albumin (BSA) at low BSP concentrations (e.g., 2 microM). Addition of increasing amounts of BSA had no effects on the maximal velocity of initial BSP uptake, but it increased the Km value from 1.5 microM (no BSA) to 24 microM (BSA/BSP molar ratio, 3.7) and 35 microM (BSA/BSP ratio, 18.4). In addition to BSP, the cloned oatp also mediated Na(+)-independent uptake of conjugated (taurocholate) and unconjugated (cholate) bile acids. Sequence analysis of the cDNA revealed an open reading frame of 2010 nucleotides coding for a protein of 670 amino acids (calculated molecular mass, 74 kDa) with four possible N-linked glycosylation sites and 10 putative transmembrane domains. Translation experiments in vitro indicated that the transporter was indeed glycosylated and that its polypeptide backbone had an apparent molecular mass of 59 kDa. Northern blot analysis with the cloned probe revealed crossreactivity with several mRNA species from rat liver, kidney, brain, lung, skeletal muscle, and proximal colon as well as from liver tissues of mouse and rabbit, but not of skate (Raja erinacea) and human.